The Role f Husnuzan and Psychological Resilience in The Quarter-Life Crisis Among Gen Z Women - Iga Nuraisyah (EDUJAVARE: International Journal of Educational Research, 2026)
The phenomenon of quarter-life crisis is increasingly experienced by Generation Z women alongside rising developmental demands, social pressures, and uncertainties in navigating early adulthood. This study aims to analyze the role of husnuzan and psychological resilience in predicting quarter-life crisis among Generation Z women. This study employed a quantitative correlational design using multiple linear regression analysis. The sampling technique used was convenience sampling, with a total of 400 Generation Z women as respondents. The results of the regression analysis indicate that, simultaneously, husnuzan and psychological resilience form a significant predictive model of quarter-life crisis (F = 8.967; p < 0.001). Partially, psychological resilience demonstrates a significant negative predictive role (β = -0.216; p < 0.001), indicating that higher levels of psychological resilience are associated with lower levels of quarter-life crisis. Meanwhile, husnuzan does not show a statistically significant role (β = 0.019; p = 0.736); therefore, within this research model, husnuzan does not function as a direct predictor of quarter-life crisis. The R Square value of 0.043 indicates that husnuzan and psychological resilience collectively explain 4.3% of the variance in quarter-life crisis, while the remaining 95.7% is influenced by other factors beyond the scope of this research model. Nevertheless, based on theoretical frameworks and previous research findings, husnuzan is understood as a cognitive-spiritual attitude associated with meaning-making, acceptance, and adaptive emotional regulation, suggesting the possibility of an indirect role. Thus, this study highlights the importance of psychological resilience in addressing quarter-life crisis and indicates that the role of husnuzan in this context requires a more comprehensive analytical approach to be fully understood